Stand and deliver - Menendez, Ramon (Philippines : Warner Home Video, 2006)
Stand and Deliver does just that. This moving, acclaimed crowd pleaser is the dynamic saga of real-life heroes determined to conquer a few people dare confront: the National advanced Placement Calculus Exam. Edward James Olmos (1998 Best Actor Academy Award Winner Nominee) gives a performance of fire and grit as Jaime Escalante, a math teacher at East Los Angeles Garfield HIgh who refuses to write off his inner - city students as losers. Escalante cajoles, pushes, threatens and inspires 18 kids who were struggling with fractions to become math whizzes. Lou Diamond Phillips and Andy Garcia co-star in this "Rocky of the classroom" (Pat Collins, WWORTV) NO doubt about it: You'll stand and cheer!